2011
DOI: 10.1097/icu.0b013e3283499409
|View full text |Cite
|
Sign up to set email alerts
|

Orbital implants for fracture repair

Abstract: The appropriate choice of orbital implant for fracture repair ensures appropriate orbital reconstruction in an effort to alleviate diplopia, enophthalmos, orbital dystopia, and extraocular muscle restriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 77 publications
0
35
0
4
Order By: Relevance
“…Some studies have also shown that Ca and Si ions play important roles in the formation of the apatite layer, and affect the biological metabolism of osteoblastic cells which indirectly influenced the mineralization process and bone-bonding mechanism (Mohammadi et al, 2014). However, the slightly faster degradation rate which mismatches with the bone tissue regeneration during the new bone ingrowth (Xu et al, 2008), especially, the relatively low fracture strength and toughness which fails to meet the specific mechanical requirement in thin-wall bone defects constrains its clinical applications (Bratton and Durairaj, 2011). To reinforce the structure and to enhance the mechanical strength, biopolymer (Shirazi et al, 2014b), metallic oxide (Shirazi et al, 2014a) and many other materials are used to modify the CSi based materials scaffolds (Mehrali et al, 2013).…”
mentioning
confidence: 99%
“…Some studies have also shown that Ca and Si ions play important roles in the formation of the apatite layer, and affect the biological metabolism of osteoblastic cells which indirectly influenced the mineralization process and bone-bonding mechanism (Mohammadi et al, 2014). However, the slightly faster degradation rate which mismatches with the bone tissue regeneration during the new bone ingrowth (Xu et al, 2008), especially, the relatively low fracture strength and toughness which fails to meet the specific mechanical requirement in thin-wall bone defects constrains its clinical applications (Bratton and Durairaj, 2011). To reinforce the structure and to enhance the mechanical strength, biopolymer (Shirazi et al, 2014b), metallic oxide (Shirazi et al, 2014a) and many other materials are used to modify the CSi based materials scaffolds (Mehrali et al, 2013).…”
mentioning
confidence: 99%
“…The use of three-dimensional reconstruction in CT imaging and virtual planning offers accurate and individualized assessment and planning for the restoration of orbital walls and orbital volume. 82,83 Since more complex preoperative planning and intraoperative navigation have become available, it has been demonstrated repeatedly that CAS is helpful in achieving more predictability in orbital reconstruction. 83,84 One of the greatest advantages of CAS is the possibility of checking the implant fit preoperatively in a digital environment.…”
Section: Technological Advantagesmentioning
confidence: 99%
“…Zu den Vor-und Nachteilen der einzelnen Materialien wird darauf verwiesen [10,21,27]. Mayer et al [19] haben 153 Patienten (Antralballon vs. Implantat) aus opththalmologischer Sicht analysiert und bescheinigen dem Antralballon bei kleinen und mittelgroßen Frakturen gute funktionelle Resultate.…”
Section: Implantatmaterialienunclassified
“…Die Anforderungen an ein ideales Material (l " Abb. 4) sind vielfäl-tig und werden von keinem Material alleine vollständig erfüllt [10,21]. Eine besondere Berücksichtigung bei der Diskussion der Materialien erfährt die Deformation des Rekonstruktionsmaterials, welche von der Defektgröße, der Dicke und den mechanischen Eigenschaften des Materials sowie von intraorbitalen Druckverhältnissen (in Ruhe 13 mmHg, jedoch nicht konstant; Valsalva!)…”
Section: Implantatmaterialienunclassified
See 1 more Smart Citation